Science Literacy -Based Pocket Book on Environmental Pollution and Climate Change in Junior High Schools - Nur Halimah; Imam Mahadi; Fitra Suzanti (Universitas Riau, 2023)
Research on the development of an integrated science pocket book based on scientific literacy on environmental pollution and climate change aims to see the validity, practicality and response of students. This study used ADDIE's research development (R&D) which consisted of Analysis, Design, Development, Implementation, and Evaluation. But in this research only reached the development stage. Data is collected through a questionnaire. After analyzing the needs and designing an integrated science literacy-based pocket book, the research proceeded to the development process. Scientific literacy consists of 4 aspects, each aspect has its own indicator code. At the pocket book development stage it was validated by five experts, namely, material experts, media experts and 2 teachers. The results showed that the validation of material, media, pedagogic experts , and 2 teachers was 3.42 with a very valid category. The results of the practicality test obtained a score of 81.84 which can be categorized as very practical, and the results of the student response test obtained a score of 86.05 in the very good category . In conclusion, the development of integrated science pocket books based on scientific literacy on environmental pollution and climate change is stated to be very valid, practical and very well used by students in the learning process.